"Breaking a Dog’s Neck" as a Metaphor for Oppressing the Weak. An Exegetical-Historical Analysis of the Expression ערף כלב (Isa 66:3) - Jędrzejczak, Andrzej Łukasz (The Biblical Annals, 2025)
This paper analyses Isa 66:3 and presents a new interpretation of the expression ערף כלב “breaks a dog’s neck.” There are various proposals to explain this enigmatic expression. One points, for example, to a possible ritual in which dogs were to be sacrificed by breaking their necks. This ritual was supposed to have been practised in the ancient Levant, including the Israelites/Judahites. This explanation is called into question in this article. It is pointed out that the phrase can be understood as a metaphor for people who impinge on the dignity of others. The exegesis of biblical texts, the examples cited from ancient Near Eastern literature, and the analysis of archaeological material indicate that this expression may have a different meaning from that hitherto accepted.